O lugar do jornalismo diante das emergências socioambientais nos discursos de repórteres - Silva, Anna Júlia Carlos da (2024)
In this dissertation, we analyze how the journalist-subject engaged in covering emerging socio-environmental issues verbalizes their practice and profession. The study focuses on the discourses of Eliane Brum, Jonathan Watts, Veronica Goyzueta, Talita Bedinelli, and Carla Jiménez, co-founders of the independent amazonian platform Sumaúma: Journalism of the Center of the World. The reading gesture devoted to the expressions of these professionals occurs through the activation of the theoretical-methodological device of french Discourse Analysis (DA), in its Pecheutian strand, especially with the guidance and operationalization of the concept-notions of subject, place, and resistance. The corpus consists of discursive sequences (DSs) excerpted from self-referential publications on the Sumaúma website. The textual sample, temporally delimited by the platform’s first year of activity – from september 2022 to september 2023 – comprises 15 journalistic articles collected from the sections entitled Manifest and Our Voice. Through the analytical, attentive, and successive reading of this material, 259 DSs were identified, pointing to twenty cores of meaning, which we named as capitalism, war, death, and struggle; decoloniality, territory, intersectionality, and scientific legitimation; participation, support, debate, activism, and democracy; creation, renewal, life, and temporality; and identity, positioning, and method. These regularities enabled the identification, classification, and naming of five subject-positions: urgency and resistance, change of perspectives, collective action, creation of futures, and journalistic doing. Based on these approaches, we identified and named the social place as journalism, the discursive place as transformation, the discursive formation as transformation, and the subject-form as a potential transformer. The results of this reading gesture, developed based on DA, were also interpreted in conjunction with an environment of discussion grounded in the socio-environmental approach to journalism and Latin American theoretical thinking, especially in its critical-utopian and decolonial currents. With the justification of contributing to thinking about the field and responding to journalistic demands arising from contemporary emergencies in Latin America, the dissertation delves deeply into the discussion of the reporting method of independent and non-hegemonic Latin American platforms; unveils the resistance of this type of initiative to traditional structures in journalism; points to the potentialities of the field in seeking social, environmental, economic, and political transformation; and demonstrates how journalistic practice is not only an institutional activity but also an expression of professionals’ subjectivity, directly related to the social and discursive context of a specific space and time.